A Review Study of New Numerical Methods for Solving Differential Equations with Impetus of Inter Disciplinary Applications with MATLAB - et. al., Jitendra Binwal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we present a review study of new numerical methods to solve ordinary differential equations in both linear and non-linear cases with impetus of inter disciplinary applications with MATLAB. We use and apply Daftardar - Gejji technique on theta-method to derive a new family of numerical method in form of review study. It is shown that the method may be formulated in an equivalent way as a Runge-Kutta method. The Stability of the method is analyzed.